2019
DOI: 10.1002/solr.201900384
|View full text |Cite
|
Sign up to set email alerts
|

Polyfluorene Copolymers as High‐Performance Hole‐Transport Materials for Inverted Perovskite Solar Cells

Abstract: Inverted perovskite solar cells (PSCs) that can be entirely processed at low temperatures have attracted growing attention due to their cost‐effective production. Hole‐transport materials (HTMs) play an essential role in achieving efficient inverted PSCs, as they determine the effectiveness of charge extraction and recombination at interfaces. Herein, three polyfluorene copolymers (TFB, PFB, and PFO) are investigated as HTMs for construction of inverted PSCs. It is found that the photovoltaic performance of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 56 publications
0
13
0
Order By: Relevance
“…73 This study revealed the proof of concept that oxide NPs can improve wetting of the precursor solution on PTAA. 73,74 Nevertheless, all layers of the presented devices were deposited mainly in the standard (n-i-p) device architecture 71,72 and merely by hardly scalable spin coating 73,74 without a full investigation on a scalable printing technique.…”
Section: Introductionmentioning
confidence: 99%
“…73 This study revealed the proof of concept that oxide NPs can improve wetting of the precursor solution on PTAA. 73,74 Nevertheless, all layers of the presented devices were deposited mainly in the standard (n-i-p) device architecture 71,72 and merely by hardly scalable spin coating 73,74 without a full investigation on a scalable printing technique.…”
Section: Introductionmentioning
confidence: 99%
“…[ 17 ] Moreover, previously reported work indicated that trap states mainly located at the interfaces of multilayers of whole device (called interface defects) and at the perovskite surface (called surface defects), which are effectively related to the energy level matching, hysteresis, charge carriers dynamics, and the long‐term environmental and operational stability. [ 18–22 ] Therefore, it is indispensable to explore an impressive way to diminish the defects, particularly at the interfaces, for acquiring the high‐efficient and stable PSCs. Currently, there are lots of approaches to improve the performance and stability of PSCs, containing additive engineering, using additive into a perovskite absorber layer and interface engineering, modifying the hole transport layer (HTL)/perovskite or perovskite/electron transport layer (ETL) interfaces.…”
Section: Introductionmentioning
confidence: 99%
“…Hybrid perovskite solar cells (PSCs) have emerged as promising candidates for the next-generation thin-film solar technologies, mainly due to their low-cost materials, simple solution fabrication process and high power-conversion-efficiency (PCE). The certified PCE of PSCs has skyrocketed from 3.8% to an impressive level of 25.2% in the past decade [1][2][3][4], which is enabled by a combined efforts in optimizing the perovskite compositions [5], interface engineering [6][7][8][9][10][11][12], and defect passivation [13][14][15]. In particular, thin films of polycrystalline perovskite processed from solution tend to produce high density of defects and exhibit a large degree of electronic disorder.…”
Section: Introductionmentioning
confidence: 99%